USING GUESSING WORDS IN TEACHING NARRATIVE TEXT TO IMPROVE READING COMPREHENSION OF THE ELEVENTH-GRADE STUDENTS - Hartati, Sri (English Community Journal, 2019)
The title of the research is “Using Small Guessing Words in Teaching Narrative Text to Improve Reading Comprehension of the Tenth Grade Students”. The problem in this research was formulated into a question: “Is it effective to improve students reading comprehension using Guessing Words from the Context to the eleventh-grade students of SMA Negeri 9 Palembang?” The Objective of this research was to find out whether or not it is effective to improve students’ reading comprehension using Guessing Words from the Context to the eleventh-grade students of SMA Negeri 9 Palembang. This research used the design of the quasi-experimental method. Researchers collected the data by using a written test. The result of the research was the students’ score in the experimental and the control group (value of t-obtained) using independent sample test was 4.341, it was higher than the critical value 2.000, at the significant level p<0.05. It was effective to improve students’ reading comprehension using Guessing Words from the Context to the eleventh-grade students of SMA Negeri 9 Palembang.